The Second Five Year Development Plan Education Department Himachal Pradesh - Planning Commission (Planning Commission, 1955)
The First Five Year Plan of Educational development in Himachal Pradesh provided Rs.49.4 lakhs while the Second Five Year Plan has been prepared at a cost of Rs.120 lakhs. This is an increase of about three times but it still will not achieve all the educational requirements of the Pradesh. The schemes included in the Second Plan will, nevertheless, provide facilities for different stages of Education.
Education Department Himachal Pradesh